The Immune Epitope Database (IEDB): 2018 update. Issue Volume 47:Issue D1(2019) (24th October 2018) - Vita, Randi; Mahajan, Swapnil; Overton, James A; Dhanda, Sandeep Kumar; Martini, Sheridan; Cantrell, Jason R; Wheeler, Daniel K; Sette, Alessandro; Peters, Bjoern
Abstract: The Immune Epitope Database (IEDB, iedb.org) captures experimental data confined in figures, text and tables of the scientific literature, making it freely available and easily searchable to the public. The scope of the IEDB extends across immune epitope data related to all species studied and includes antibody, T cell, and MHC binding contexts associated with infectious, allergic, autoimmune, and transplant related diseases. Having been publicly accessible for >10 years, the recent focus of the IEDB has been improved query and reporting functionality to meet the needs of our users to access and summarize data that continues to grow in quantity and complexity. Here we present an update on our current efforts and future goals.